m6A modification on the fate of colorectal cancer: functions and mechanisms of cell proliferation and tumorigenesis - Jiang, Xiaohan; Jin, Ziyao; Yang, Yuzhong; Zheng, Xiang; Chen, Shaohua; Wang, Shuaijie; Zhang, Xuemei; Qu, Nanfang (Frontiers in Oncology, 2023)
N6-methyladenosine (m6A) is the most pervasive RNA modification in eukaryotic cells. The dynamic and reversible m6A modification of RNA plays a critical role in tumor occurrence and progression by regulating RNA metabolism, such as translocation, mRNA stability or decay, pre-mRNA splicing, and lncRNA processing. Numerous studies have shown that m6A modification is involved in the development of various cancers. This review summarizes the major role of m6A modification in CRC proliferation and tumorigenesis and the prospect of modulating the m6A modification for tumor treatment. These findings will provide new therapeutic strategies for clinically translating the use of m6A modification for CRC in the near future.